2007
DOI: 10.1590/s1676-26492007000500006
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and mood disorders in psychogenic nonepileptic seizures

Abstract: The diagnosis of psychogenic nonepileptic seizures (PNES), particularly in patients with epilepsy, poses a special challenge to the physician in care of these patients. Psychiatric disorders (PD) are more common among patients with epilepsy than in the general population, and this appears to be even more important in patients with PNES. Depression and other mood disorders, as well as anxiety disorders -particularly panic attacks -may make the management of these patients even more difficult in the clinical pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…As such, the demographic differences in the samples could account for the difference in levels of depression between PWE and pwPNES observed in this review. However, it is important to note that up to 80% of pwPNES are female [2] and therefore the observed differences may reflect a reliable difference between populations of pwPNES and PWE.…”
Section: Critiquementioning
confidence: 96%
See 1 more Smart Citation
“…As such, the demographic differences in the samples could account for the difference in levels of depression between PWE and pwPNES observed in this review. However, it is important to note that up to 80% of pwPNES are female [2] and therefore the observed differences may reflect a reliable difference between populations of pwPNES and PWE.…”
Section: Critiquementioning
confidence: 96%
“…Mood disorders (including major depression) are the most common with a prevalence of 24.4%/14.1% (lifetime/past year) in PWE, as compared to 13.2%/5.2% in the general population [1]. Similarly, co-morbid psychiatric disorders are more common in pwPNES than in the general population and again, depression is the most common psychiatric disorder with an average prevalence of 31% and lifetime rates ranging from 36 to 80% [2].…”
Section: Introductionmentioning
confidence: 99%
“…Stressing the treatment gap for PNES, literature in LA, largely from Argentina and Brazil, reveals that vEEG usage is highly suggested as a diagnostic tool (where available) to correctly diagnose the patients [10,[13][14][15]25,26,[28][29][30][31][32][33][34]. Studies in LA have identified higher frequencies of psychiatric comorbid diagnoses, such as anxiety and dissociation, than studies in the US [11,15,25,27,35,36]. Moreover, reports in LA of trauma and abuse, such as physical or sexual abuse, reveal lower frequencies [13,25,35] than those reported in the US [14,37].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal behaviors including crying, shouting, laughing as well as other uncontrollable behaviors observed in our study. In reported semiological classifications for PNES, such kind of symptoms were considered as emotional or psychological disorders ( 32 , 33 ), meanwhile, they were re-defined in our study with respect to behaviors rather than triggers. Importantly, as abnormal behaviors were also seen in immune encephalitis patients ( 34 ), the involvement of immune encephalitis should be examined for better diagnosis.…”
Section: Discussionmentioning
confidence: 99%